Review of Different Criteria for Designing Routing Protocols - Saroj, Suman; Tiwari, Raj Gaurang; Kumar, Pankaj (International Journal of Computer Sciences and Engineering, 2025)
Routing is the process of finding optimal path between source and destination. Because of the fact that packet may be necessary to hop or several hops before a packet reach the target, a routing protocol is needed. Routing protocols allow routers to dynamically advertise and discover routes, decide which routes are available and which are the most efficient routes to a target. In this paper we review different existing protocols and their applicability in current scenario.